DDNS + gateway separation method for interconnect of distributed data center - Sheng-jun XIE; Li-ping CAI; Feng YIN (Tongxin xuebao)
The multi-campus university distributed data centers interconnected problems existing in the traditional gateway were analyzed and based on RHI + gateway unilateral separation methods on the Internet,a DDNS + gateway interconnection separation idea to front-end technology was proposed to achieve business traffic sites DDNS selection,using the device with the VMware SLB to achieve uninterrupted user access.In a lab environment,online or new on-line users drifting around in a virtual machine can fast access to the data center to the same kind of business,suitable for the business flow,IP planning complex continuous demanding scenarios.The interconnection method must increase DDNS equipments in the data center edge,hanging the SLB device next to the switch side of data centers in both places.